STUDI KEPUASAN PENGGUNA LULUSAN PROGRAM STUDI PENDIDIKAN TEKNIK BANGUNAN JURUSAN TEKNIK SIPIL FT UNJ - Tri Oke Mahendra; Gina Bachtiar; Eka Murti Nugraha (LPPM Universitas Negeri Jakarta, 2012)
The purpose of this research is getting the data about the level of complacency of User to the alumni of Building Engineering Education Department of Civil Engineering Faculty of Engineering State University of Jakarta. The population of this research is formal and informal institutions which use about 30 alumni as the teacher based on the data of IKA – The Alumni of Building Engineering Education Faculty of Engineering State University of Jakarta. A number of 24 educational institutions located in Jabodetabek who had used the alumni between the years 2001-2011 will be the sample of this research. The result shows that the pedagogic competency with the level of appropriateness 79.83% is quite satisfying, personal competency with level of appropriateness 87.55% is satisfying, professionalism competency with the level of appropriateness 83.23% is satisfying, and the business competency with the level of appropriateness 84.83% is satisfying based on the required competency had in the Building Engineering Education Program Faculty of Engineering State University of Jakarta. Level of interest for each competency shows that the personal competency placed in quadrant B which means this competency is the urgent competency to be had for each alumni and it is successfully performed by the alumni to reach the target of the Building Engineering Education Program. Besides, the professionalism, pedagogic, and business competency located in quadrant C meaning that this competency is important to be had for each alumni and it is not wellperformed yet by the alumni. The result of this research shows that the expectation of the alumni measured in this research based on the pedagogic, personal, professionalism, social and business competency is urgently needed to be had for the alumni of Building Engineering Education Department of Civil Engineering State University of Jakarta. The assessment of occupation from the user shows that those competencies have shown by the alumni well.